2017
DOI: 10.1080/13691058.2017.1367036
|View full text |Cite
|
Sign up to set email alerts
|

Somali American female refugees discuss their attitudes toward homosexuality and the gay and lesbian community

Abstract: Minnesota is home to the largest population of Somalis in the USA - most arriving as refugees from the civil war in Somalia. As Somali Americans adjust to life in the USA, they are likely to undergo shifts in their belief systems - including changes in their attitudes toward gays and lesbians. We examined the attitudes of 29 Somali American women in the Minneapolis-St. Paul metropolitan area toward homosexuality via face-to-face, semi-structured interviews. Transcripts were translated, transcribed and analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, a study conducted in Zambia reported that LGBT adolescents could not benefit from reproductive and sexual health services due to social stigma (Müller et al, 2018). Another study found that people who emigrated from Somalia, where Islam is dominant, to the United States, were more tolerant of LGBT people after immigration (Hunt et al, 2018). Thus, Turkey's conservative, patriarchal culture and traditional structure increase people's tendency toward homophobia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study conducted in Zambia reported that LGBT adolescents could not benefit from reproductive and sexual health services due to social stigma (Müller et al, 2018). Another study found that people who emigrated from Somalia, where Islam is dominant, to the United States, were more tolerant of LGBT people after immigration (Hunt et al, 2018). Thus, Turkey's conservative, patriarchal culture and traditional structure increase people's tendency toward homophobia.…”
Section: Discussionmentioning
confidence: 99%